Enucleation is a feasible procedure for well-differentiated pNEN: a matched pair analysis - Nießen, Anna; Bechtiger, Fabiola A.; Hinz, Ulf; Lewosinska, Magdalena; Billmann, Franck; Hackert, Thilo; Büchler, Markus W.; Schimmack, Simon (Cancers, 2022)
The extent of surgical resection in the treatment of pancreatic neuroendocrine neoplasms (pNEN) is still controversial. This study aimed to evaluate the outcomes of enucleation for well-differentiated non-functional (nf) pNEN. Patients undergoing enucleation (2001-2020) were analyzed. Clinicopathological parameters, perioperative outcomes and survival were assessed. The analysis was performed as a nested case-control study and matched-pair analysis with formal resection. Sixty-one patients undergoing enucleation were identified. Compared to patients undergoing formal resection, enucleation was associated with a significantly shorter median length of operative time (128 (IQR 95-170) versus 263 (172-337) minutes, p < 0.0001) and a significantly lower rate of postoperative diabetes (2% versus 21%, p = 0.0020). There was no significant difference in postoperative pancreatic fistula rate (18% versus 16% type B/C, p = 1.0), Clavien−Dindo ≥ III complications (20% versus 26%, p = 0.5189), readmission rate (12% versus 15%, p = 0.6022) or length of hospital stay (8 (7-11) versus 10 (8-17) days, p = 0.0652). There was no 30-day mortality after enucleation compared to 1.6% (n = 1) after formal resection. 10-year overall survival (OS) and disease-free survival (DFS) was similar between the two groups (OS: 89% versus 77%, p = 0.2756; DFS: 98% versus 91%, p = 0.0873). Enucleation presents a safe surgical approach for well-differentiated nf-pNEN with good long-term outcomes for selected patients.
Gesehen am 23.06.2022
This article belongs to the special issue "Updates on diagnostic and therapeutic management of neuroendocrine neoplasms"